2004
DOI: 10.1254/jphs.94.166
|View full text |Cite
|
Sign up to set email alerts
|

p53-Mediated Cell Cycle Arrest and Apoptosis Induced by Shikonin via a Caspase-9-Dependent Mechanism in Human Malignant Melanoma A375-S2 Cells

Abstract: Abstract. Natural products regulate cell growth in response to oncogene activation that induces cell cycle arrest and apoptosis in tumor cell lines. We investigated the mechanisms of caspase activation in human malignant melanoma, A375-S2 cells, by the natural product shikonin, which was isolated from the plant Lithospermum erythrorhizon SIEB. et ZUCC. Shikonin inhibited cell growth in a time-and dose-dependent manner, which might be mediated through up-regulation of p53 and down-regulation of cyclin-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
89
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(95 citation statements)
references
References 31 publications
5
89
1
Order By: Relevance
“…Shikonin, isolated from roots of the medicinal herb Lithosper mum er ythrorhizon Siebold Zucc [14] , is a Chinese herbal medicine with various biological activities, including anti-microbial, anti-fungal, anti-HIV, anti-inflammatory, anti-tumor, and wound-healing activities [15][16][17] . However, its toxicity has limited it as a therapeutic agent [14,17] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shikonin, isolated from roots of the medicinal herb Lithosper mum er ythrorhizon Siebold Zucc [14] , is a Chinese herbal medicine with various biological activities, including anti-microbial, anti-fungal, anti-HIV, anti-inflammatory, anti-tumor, and wound-healing activities [15][16][17] . However, its toxicity has limited it as a therapeutic agent [14,17] .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, tumorigenesis and tumor progression are strongly associated with abnormal apoptosis. It has been shown that shikonin and its derivatives induce apoptosis of tumor cells [16,19,20] . Our data demonstrate that acetylshikonin could also induce apoptosis of SGC-7901 cells with typical apoptotic alterations, including morphological changes and positive TUNEL assay, DNA fragmentation and apoptotic Apoptosis is a complex process regulated by a variety of factors [21,22] .…”
Section: Discussionmentioning
confidence: 99%
“…36 It is well established that the central role of p53 is partly associated with the regulation of cell apoptosis via Caspase-3, Caspase-9, Bcl-2 and Bax. [37][38][39] However, apoptosis with specific regard to Bcl-2 or caspase is also triggered by p53 independent manner, such as Par-4 or p21 WAF1/CIP1 pathway. [40][41][42] Cyclin B1 overexpression is usually caused by the inactive function of p53.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that the anticancer activities of shikonin derivatives may be attributed to their ability to down-regulate anti-apoptotic Bcl-2 family members, such as Bcl-2 and Bcl-xL, generate reactive oxygen species (ROS), activate caspases [11,12], inhibit EGFR phosphorylation [13] and arrest the cell cycle through p53 upregulation [14]. However, the precise mechanisms employed by shikonin to repress cancer growth remain to be defined.…”
Section: Introductionmentioning
confidence: 99%